Pengaruh Harga, Promosi, dan Label Halal terhadap Purchase Intention Produk Cushion Glad2glow: Studi Kasus pada Mahasiswi Febi UINFAS Bengkulu - Maslika Rahayu; Nonie Afrianty; Syaifuddin (CV Global Research Publication, 2026)
This study aims to determine the effect of price, promotion, and halal label on the purchase intention of Glad2Glow Cushion products among FEBI UINFAS Bengkulu students of the 2022 cohort. This research employed a causal associa-tive research design with a quantitative approach. The popu-lation consisted of all FEBI UINFAS Bengkulu students of the 2022 cohort. The sample was determined using the Slov-in formula, resulting in 75 respondents. Data were collected through questionnaires and analyzed using SPSS version 20, including multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results showed that price had a positive and significant effect on purchase inten-tion, with a t-value of 4.728 and a significance value of 0.000. Promotion also had a positive and significant effect on purchase intention, with a t-value of 4.814 and a significance value of 0.000. Halal label had a significant effect on pur-chase intention, with a t-value of -2.869 and a significance value of 0.005. Simultaneously, price, promotion, and halal label significantly affected purchase intention, with an F-value of 30.863 and a significance value of 0.000. The Ad-justed R Square value of 0.511 indicates that price, promo-tion, and halal label explain 51.1% of the variation in pur-chase intention, while the remaining 48.9% is influenced by other factors outside the research model.